1992
DOI: 10.1136/gut.33.5.604
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Helicobacter pylori in Peru: infection rates in coastal, high altitude, and jungle communities. The Gastrointestinal Physiology Working Group of the Cayetano Heredia and the Johns Hopkins University.

Abstract: We have examined endoscopic clinic patients in three widely different geographic regions of Peru (the coast, the Sierra of the Andes Mountains, and the Amazon jungle) for the presence of Helicobacter pylori infection associated with active gastritis. The overall rates of infection were high (80% or greater) in all three zones and rates for men were approximately 10% higher than for women in the same zone. Men and women in the Sierra and jungle areas had significantly higher rates of infection than did those on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Previous studies have reported sex differences in H. pylori infection prevalence in Amazonian communities, though the literature is limited. Ramirez‐Ramos et al (1992) investigated the prevalence of H. pylori infection associated with active gastritis in three geographic regions in Peru. They found that male participants had H. pylori infection rates that were approximately 10% higher than females.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported sex differences in H. pylori infection prevalence in Amazonian communities, though the literature is limited. Ramirez‐Ramos et al (1992) investigated the prevalence of H. pylori infection associated with active gastritis in three geographic regions in Peru. They found that male participants had H. pylori infection rates that were approximately 10% higher than females.…”
Section: Discussionmentioning
confidence: 99%
“…China exhibits a clear geographical clustering in the distribution of CAG and GC, with Fujian province standing out as a high-incidence area for this condition in the country (Li et al, 1996 ; Yang, 2006 ). The H. pylori infection is an important risk factor for CAG, affecting approximately half of the world's population, but the prevalence varies in different geographic regions (such as coastal, high altitude, and jungle; 1992 ; Yin et al, 2022 ; Malfertheiner et al, 2023 ). H. pylori infection is highly prevalent in coastal areas of China, such as Hainan and Shenzhen, with a high incidence rate among asymptomatic individuals (Li et al, 2022 ; Chen et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%